Description of Parenteral Anxiety With Children Who Will Undergo Anxiety - Sukma Satriyawan, Ade; Lintang Suryani, Roro; Novitasari, Dwi; Suandika, Made (Java Nursing Journal, 2024)
Background: Pediatric pain associated with invasive medical procedures is a significant cause of anxiety for parents. Most parents experience preoperative anxiety and fear. Purpose: The study aims to describe the anxiety of parents with children who will undergo anesthesia at IBS RSU Afdila Cilacap 2023. Methods: The research conducted is Quantitative research with descriptive design. The approach that will be used during the research is cross sectional, the sample in this study is using the Total Sampling method as many as 31 respondents. Data were collected using a questionnaire instrument used in this study, the Indonesian version of the Hamilton Anxiety Rating Scale (HARS) parental anxiety questionnaire sheet. Result: The results of most of the moderate anxiety were 17 respondents (54.8%), at the age of the child most children aged 12-18 years with moderate parental anxiety as many as 9 respondents (29.0%), in the gender of the parents most female gender with moderate anxiety as many as 12 respondents (38.7%), the employment of parents most private jobs with moderate anxiety as many as 12 respondents (38.7%). Conclusion: there is still severe anxiety in as many as 7 respondents from this study, so there must be treatment or intervention to reduce parental anxiety in children who will undergo surgery.